Is there a difference between tranexamic acid application routes in hip hemiarthroplasty? - Yerli, Mustafa; İmren, Yunus and Çabuk, Haluk and Dedeoğlu, Süleyman Semih and Yüce, Ali and Bayraktar, Tahsin Olgun and Erkurt, Nazım and Gürbüz, Hakan (The European Research Journal, 2022)
Objectives: This study aimed to define the optimal efficacy route of tranexamic acid treatment given during hemiarthroplasty after femoral neck fracture. Methods: This study examined the files of patients with hip fractures over 65 years of age and treated surgically in our clinic between 2017 and 2019. Patients included in these files were grouped as non-tranexamic acid and topical and systemic tranexamic acid. Then, the demographic information, height and weight of the patient files, haemoglobin and hematocrit levels before and after the surgery, bleeding profiles, tranexamic acid dose and the route of administration, complications in postoperative follow-up, the amount of fluid coming from the drain and duration of drainage, postoperative intensive care follow-up duration of hospitalisation was investigated. Results: A total of 100 patients, 50 of whom were in the control group, 25 of whom were treated with topical tranexamic acid, and 25 of whom were treated with intravenous tranexamic acid, were included in this study. Postoperative blood transfusion was applied to 60% (n = 30) of the control group, 20% (n = 5) of the topical group, and 24% (n = 6) of the intravenous group. When compared statistically, it was found that topical and intravenous groups were lower than the control group (p = 0.001 and p = 0.002, respectively), but there was no significant difference between them (p = 0.759). When the blood loss calculations made by the Gross method were examined, the average of the control group was 1011.5 ml (179-1837 ml), the topical group was 695.7 ml (11-2503 ml), and the intravenous group was 710.9 ml (173-11315 ml) calculated as. When analysed statistically in terms of blood loss, it was found that the control group was significantly higher than the topical and intravenous groups, but there was no significant difference between the topical and intravenous groups (p = 0.002). Conclusions: Tranexamic acid applied to reduce blood loss during arthroplasty surgery can be used effectively either by topical or systemic methods.